Investigating genetic variants in microRNA regulators of Neurokinin‐1 receptor in sudden infant death syndrome. (2nd November 2022) - Shaukat, Zeeshan; Byard, Roger W.; Vink, Robert; Hussain, Rashid; Ricos, Michael G.; Dibbens, Leanne M.
Abstract: Sudden infant death syndrome (SIDS) occurs more often in male than in female infants, suggesting involvement of the X‐chromosome. Histopathological studies have suggested that altered expression of the Neurokinin‐1 receptor may also play a role in the pathogenesis of SIDS. It was hypothesised that genetic variants in three X‐chromosome‐encoded microRNA (miRNA/miR), known to down‐regulate expression of the Neurokinin‐1 receptor, may contribute to SIDS. Aim: To identify sequence variants in the miRNAs within a study cohort (27 cases of SIDS and 28 controls) and determine if there was a difference in the frequencies in male and female SIDS infants. Methods: Genomic DNA prepared from stored blood spots was amplified and sequenced to identify genetic variants in miR500A, miR500B and miR320D2. Results: No novel variants in the miRNAs were identified in our study cohort. We identified one known single‐nucleotide polymorphism (SNP) in miR320D2: rs5907732 G/T, in both cases and controls. No significant difference in the SNP frequency was observed between male and female SIDS cases. Conclusion: This pilot study suggests that sequence variants in three miRNAs do not contribute to the reported higher prevalence of SIDS in male infants and do not contribute to the pathogenesis of SIDS in our cohort.